2001
DOI: 10.1002/nur.10010
|View full text |Cite
|
Sign up to set email alerts
|

Clinical trials in the 21st century: The case for participant‐centered research¶

Abstract: Informed consumers of the 21st century increasingly will be hesitant to enroll in randomized clinical trials (RCTs) because they will be unwilling to (a) submit to random assignment; (b) complete assessments that are too lengthy, intrusive, or irrelevant; or (c) comply with protocols that do not meet their needs. Research centered on the needs and interests of participants is likely to engender greater participation and commitment than are traditional RCTs. Recommendations for making clinical trials more parti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
63
0

Year Published

2003
2003
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 61 publications
(63 citation statements)
references
References 37 publications
0
63
0
Order By: Relevance
“…Randomization of patients into clinical trials however precludes patient choice and therefore may result in resistance to participation in clinical trials [35]. The perception of treatment as a threat to freedom of choice has been correlated with poor compliance in some vulnerable populations [36].…”
Section: Random Approachmentioning
confidence: 99%
See 1 more Smart Citation
“…Randomization of patients into clinical trials however precludes patient choice and therefore may result in resistance to participation in clinical trials [35]. The perception of treatment as a threat to freedom of choice has been correlated with poor compliance in some vulnerable populations [36].…”
Section: Random Approachmentioning
confidence: 99%
“…The perception of treatment as a threat to freedom of choice has been correlated with poor compliance in some vulnerable populations [36]. Participant-centered clinical research, which addresses the patients' goals, interests, and abilities has been advocated by some authors [35]. Not only is it proposed that this decreases attrition from clinical trials, but may also align the research strategy with the patient's goals of care.…”
Section: Random Approachmentioning
confidence: 99%
“…Some of these articles focus upon obtaining informed consent and working participant-centred [7,8,13]. Wilkes and Beale [42] found that one ethically troubling situation for research nurses can be the experienced role conflict between being a nurse providing care and being a research assistant.…”
Section: Introductionmentioning
confidence: 98%
“…Some of the cited authors were making such a call (e.g., Gross & Fogg, 2001), but many were not. Instead, they were asking for consideration of ways to improve how RCTs are conducted.…”
Section: Lack Of Precision In Language Argumentmentioning
confidence: 99%